Considerações sobre o populismo na política do Espírito Santo (1959-1966) - Alvarenga, Jefferson Ferreira (2012)
This work tries to understand the populism aspects of politics in the state of Espírito Santo, taking in consideration the structure of the period of time between 1959 and 1966, which considers the governments of Carlos Lindenberg (1959-1962) and Francisco Lacerda de Aguiar (1963-1966). Here also, we analisethe aspects, of behavior of those political leaders and their own politics projects beyond of transformation of the local society. In other words, feeling how those leaders behave before the transformation of traditional/agrarian society to urban/industry society. To compare the action of those two governments, we used as primary and secundary sources, the Biblioteca Pública Estadual, in Assembleia Legislativa of Espírito Santo. So we start from the hypothesis: the populism, was different of ordinary model present in the southeast region, caused by its peculiarity that came out of its social and historical generation process. In that process we observed the domain of class linked to production and exportation coffee, in the economic field as well as the political structure. This supremacy generates difficulties to populism manifestation as a political experience, and forces the creation of link between the coffee Elite and government leaders. Nevertheless, that capitalist industry transformation in curse in the country, since the fifties, as well as the coffee crisis initiated in 1955, and the urbanization process imposed to the political leaders change their political praxis, because of the new and consolidated economical and sociopolitical environment. This new and heterogeneous social environment gives to those leaders, Carlos Lindenberg and Francisco Lacerda an opportunity to modify their political praxis and gives to them other direction, toward rural and urban population, making these support fundamental, like coffee elite support. Such changes resulted in many benefits to society, like better health assistance, education, sanitation, etc. However, the populism experience in the Espírito Santo state decays with the Military movement of 1964. Although governor Lacerda gave support to the movement, the conflicts between the populism and the military practice became apparent in 1965 with corruption complaints, resulting his resignation. We can deduce that the populism in the state of Espírito Santo is a result of a complex transformation which involves many variables in the social, political and economical fields. Yet in that populism we can find that the urban and rural masses and the coffee class, work together. Because this complexities, these two leaders in many opportunities changed their strategies to keep their position power in, in the middle of that ambiguous conjucture.